The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.mce.2020.111082
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1 phosphate induces cAMP/PKA-independent phosphorylation of the cAMP response element-binding protein (CREB) in granulosa cells

Abstract: Background and aims: Sphingosine-1 phosphate (S1P) is a lysosphingolipid present in the ovarian follicular fluid. The role of the lysosphingolipid in gonads of the female is widely unclear. At nanomolar concentrations, S1P binds and activates five specific G protein-coupled receptors (GPCRs), known as S1P 1-5 , modulating different signaling pathways. S1P 1 and S1P 3 are highly expressed in human primary granulosa lutein cells (hGLC), as well as in the immortalized human primary granulosa cell line hGL5. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 78 publications
(96 reference statements)
1
6
0
1
Order By: Relevance
“…This observation indicates a possible important role of S1P in protection of human beta-cells against cytokine toxicity, since in human beta-cells cytokines exert their toxic effects without induction of the iNOS pathway [50,135,136]. Exposure of INS1E cells to S1P results in an increased cAMP generation [30], extending the earlier observations that S1PR2 activation induces cAMP production in other cell types [137][138][139][140]. It has been demonstrated that HDL, which is enriched in S1P through its binding to apoM, could counteract beta-cell apoptosis induced by cytokines [141].…”
Section: Extracellular S1psupporting
confidence: 65%
“…This observation indicates a possible important role of S1P in protection of human beta-cells against cytokine toxicity, since in human beta-cells cytokines exert their toxic effects without induction of the iNOS pathway [50,135,136]. Exposure of INS1E cells to S1P results in an increased cAMP generation [30], extending the earlier observations that S1PR2 activation induces cAMP production in other cell types [137][138][139][140]. It has been demonstrated that HDL, which is enriched in S1P through its binding to apoM, could counteract beta-cell apoptosis induced by cytokines [141].…”
Section: Extracellular S1psupporting
confidence: 65%
“…Furthermore, phosphorylation of transcription factors CREB and ATF-2 by PClP was similar to isoprenaline activation ( Figure 4 C). Phosphorylation of CREB can involve multiple pathways, some of which are independent of both cAMP induction and PKA activation [ [24] , [25] , [26] ]. We thus further aimed to delineate the mechanism responsible for PClP-mediated phosphorylation on canonical PKA substrates.…”
Section: Resultsmentioning
confidence: 99%
“…In a word, the LHCGR-provoked cAMP, which spreads throughout the follicle is critical to identify the mechanisms involved in the pathogenesis of unruptured follicles, especially after LH surge. Previous studies have originally confirmed that cAMP signaling can increase the transcriptional activity of cAMP-response element-binding protein (CREB) ( 46 ), but recent researches provide compelling evidence that C/EBPs also serve as cAMP-responsive transcription factors due to their functionally cAMP-inducible activities ( 47 ). Occupying specific cis-elements in the cAMP response unit (CRU), C/EBPα has proved to play a critical role in this process ( 48 ).…”
Section: Discussionmentioning
confidence: 99%